Fatigue substantiation and damage tolerance evaluation of rotorcraft horizontal tail - Kumar, R.V.; Godines, C.; Abdi, F. (My University, 2017)
To ensure safe operation of the helicopter throughout its lifetime the primary structure has to be designed taking into account damage tolerance criteria. This has been considered in the design process for example by using multiple load paths as well as by taking into account the presence of certain structural defects like impacts or manufacturing defects in composite parts when performing the dimensioning and lifetime calculations. This paper describes and presents an effort performed for Damage Tolerance (DT) aspects of rotorcraft Horizontal Tail (HT) through Multi-Scale (MS) modeling computational approach to assess the growth rate of damages from fatigue under spectrum loading from rotorcraft mission profile and consideration of the effects of material variability to assess structural advantages. Main emphasis was laid on the design of the cyclic loaded components in order to achieve unlimited life with high flaw tolerance. A micromechanics based Multi-Scale Progressive Failure Analysis (MSPFA) approach that detects damage and fracture evolution is carried out to assess the Durability and Damage Tolerance (D&DT) of HT with effect of defects: 1) ply-drop-off, and features at the reduced skin thicknesses along the length of spar; 2) fiber waviness exhibited in thick sections; and 3) void shape, size, distribution. Fatigue life is estimated under service spectrum block loading conditions in critical mission by determining the material stiffness and strength degradation, failure load and cycles